The Impact of Purbalingga Regency Superior Product Aid on Batik, Bamboo, and Sculpture Crafts after the Covid-19 Pandemic - Wawan Kurniawan; Dede Nurdiawati; Noviea Varahdilah Sandi; Sugeng Riyanto (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
The COVID 19 pandemic has had a big effect on Indonesia's small and medium-sized enterprises (SMEs), including changes in people's buying power, turnover, SME output, and numerous other unprofitable changes, especially in Purbalingga SMEs. This community service is aimed at increasing the competitiveness of the superior products of Purbalingga Regency through increasing the value of products in Small and Medium Enterprises (UKM) of Batik, Bamboo, and Sculpture Crafts. The program was carried out by counseling and mentoring methods, by utilizing technology efficiency, training in the use of tools, and optimization of partnerships. The results achieved include the successful implementation of new strategies to survive in new normal conditions, starting from changing the function of the product, carrying out the collaboration between batik, bamboo and wood craftsmen, and more intensive online marketing, collaborating, implementing creativity and innovation that increase product value, so that the turnover and quality of superior products increases and has high competitiveness.